2022
DOI: 10.1111/jocd.15472
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in skin quality parameters in postmenopausal participants after use of topical growth factor serum

Abstract: Background Photodamage can induce skin aging processes that can be particularly concerning for postmenopausal women. Growth factors from hypoxic human fibroblast‐conditioned media have demonstrated improvements in skin quality parameters. Aims The aim of the study was to assess efficacy and tolerability of topical combination‐treatment hypoxic growth factor serum (TNS A+) in postmenopausal women with moderate to severe facial photodamage. Patients/Methods In this 12‐week, open‐label, single‐center study, parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…Clinical studies on hypoxic FB secretome have shown significant impacts on key skin rejuvenation parameters including overall photodamage and coarse wrinkles, with patient‐reported outcomes assessing age appearance corroborating the improvements observed in grading assessments and biopsy sample analysis. In addition, similar improvements were also achieved by topical hypoxic FB secretome in post‐menopausal females 29,30 …”
Section: Collection and Characterization Of Human Dermal Fb Secretomesupporting
confidence: 52%
See 1 more Smart Citation
“…Clinical studies on hypoxic FB secretome have shown significant impacts on key skin rejuvenation parameters including overall photodamage and coarse wrinkles, with patient‐reported outcomes assessing age appearance corroborating the improvements observed in grading assessments and biopsy sample analysis. In addition, similar improvements were also achieved by topical hypoxic FB secretome in post‐menopausal females 29,30 …”
Section: Collection and Characterization Of Human Dermal Fb Secretomesupporting
confidence: 52%
“…In addition, similar improvements were also achieved by topical hypoxic FB secretome in post-menopausal females. 29,30…”
Section: Fbs Secretome As a Source Of Rejuvenating Exosomesmentioning
confidence: 99%
“…Table 1 summarizes the 33 identified studies and highlights study design, treatments, and methods of evaluation 29–62 . There were nine RCTs (7 double‐blind and 2 single‐blind) 30,32–34,37,42,46,48,56,59 and 24 CS studies 29,31,35,36,38–40,43–45,47,49–55,57,58,60–62 .…”
Section: Resultsmentioning
confidence: 99%
“…These underlying factors, exacerbated in women by declining levels of estrogen at menopause, lead to progressive loss of skin elasticity and firmness, development of fine and coarse lines and wrinkles, uneven skin tone, and sagging. [1][2][3] Consistent with these mechanisms, topical application of human fibroblast-generated growth factors has demonstrated the ability to rejuvenate aging skin. In early studies, neonatal human dermal fibroblasts cultured under normoxic physiological conditions were found to secrete a complex, balanced mixture of growth factors, cytokines, and ECM proteins involved in wound healing.…”
Section: Introductionmentioning
confidence: 87%
“…[9][10][11] HCCM-based topical formulations, used as monotherapy or as adjuncts to aesthetic procedures, have demonstrated efficacy against common signs of aging and in postprocedure healing in clinical studies. 2,[10][11][12][13][14] TNS® Advanced+ Serum (TNS A+ Serum; SkinMedica®, Allergan Aesthetics, an AbbVie Company, Irvine, CA, USA) is a novel topical hypoxic growth factor serum product containing HCCM in combination with active botanical ingredients; its development and components are described in a separate manuscript. 10 In clinical studies, TNS A+ Serum has demonstrated the ability to significantly improve multiple hallmarks of aging skin (e.g., photodamage, sagging, coarse lines and wrinkles, and fine lines and wrinkles); whereas in an in vitro human skin model, TNS A+ Serum upregulates ECM-associated genes.…”
Section: Introductionmentioning
confidence: 99%